2023
DOI: 10.1182/blood.2022016074
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral gene therapy for X-linked chronic granulomatous disease recapitulates endogenousCYBBregulation and expression

Abstract: X-Linked Chronic Granulomatous Disease (X-CGD) is a primary immunodeficiency caused by mutations in the CYBB gene resulting in the inability of phagocytic cells to eliminate infections. In order to design a lentiviral vector capable of recapitulating the endogenous regulation and expression of CYBB, a bioinformatics-guided approach was utilized to elucidate the cognate enhancer elements regulating the native CYBB gene. Using this approach, we analyzed a 600 kb topologically associated domain of the CYBB gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The primary immunodeficiency caused by mutations in the CYBB gene results in the inability of phagocytes to clear the infection ( Wong et al, 2023 ). Numerous studies have demonstrated the role of CYBB as an inflammatory factor in developing multiple diseases ( Chen et al, 2021 ; Hong et al, 2021 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary immunodeficiency caused by mutations in the CYBB gene results in the inability of phagocytes to clear the infection ( Wong et al, 2023 ). Numerous studies have demonstrated the role of CYBB as an inflammatory factor in developing multiple diseases ( Chen et al, 2021 ; Hong et al, 2021 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al took a bioinformatics-guided approach to design a lentiviral vector (LV) that can closely mimic the physiological regulation and expression of the endogenous CYBB gene. 130 This approach was rooted in identifying the enhancers that regulate the CYBB gene. An analysis of a 600-kilobase TAD surrounding the CYBB gene revealed 16 potential enhancer elements, including one in intron 3, which significantly increased expression.…”
Section: Bioinformatics-driven Design Of Lentiviral Gene Therapy For ...mentioning
confidence: 99%
“…Wong et al. took a bioinformatics‐guided approach to design a lentiviral vector (LV) that can closely mimic the physiological regulation and expression of the endogenous CYBB gene 130 . This approach was rooted in identifying the enhancers that regulate the CYBB gene.…”
Section: Precision In Practice: Highlighting Gene Therapy Innovations...mentioning
confidence: 99%
“…All genetic forms of CGD respond to transplantation, and the best outcomes are expected at a young age, before permanent organ damage has occurred [59]. For a few patients where HSCT may not be an option, e.g., because of severe pre-morbid conditions, clinical trials on gene therapy are currently underway [60,61]. However, current methods of introducing the corrected gene generally result in an increased but still sub-optimal oxidase activity, which may be sufficient to protect from infection but not the inflammatory complications previously described.…”
Section: Treatmentmentioning
confidence: 99%